Validasi Pemeriksaan Kolesterol Total Metode CHOD- PAP pada Sampel yang Disimpan Selama 1 Minggu dalam Suhu 4-8°C - Nabilla, Jihan; Ulya, Nabila Intifa; Ardianty, Rieke Rofikoh; Agiska, Sabrina Dela; Nadifah, Fatkhatin; Qomariyah, Nurul (Jaringan Laboratorium Medis, 2023)
High total cholesterol levels cause various diseases, especially those related to the heart  and blood vessels. Total cholesterol test uses serum as a sample and must be analyzed within one hour after sampling.However, in the field sometimes there are inspection delays.Some studies have proven that serum stored for one week at a temperature of 4-8°C has different results in total cholesterol examination. For this reason, this study aims to determine the validity of total cholesterol examination using the CHOD-PAP method of serum samples stored for one week at a temperature of 4o-8oC. Validation test based on eight parameters, there are precision, accuracy, linearity, reportable range,limit detection, quantitation limit,  recovery, and interference. Only the recovery test was not accepted from eight parameters. Based on the Kruskal Wallis test, the sig value is 0.172 <0.05, it can be stated that there is no difference in serum storage time for one week at a temperature of 4-8℃ on total cholesterol levels using CHOD-PAP method.